Critical features of peer assessment of clinical performance to enhance adherence to a low back pain guideline for physical therapists: a mixed methods design. Issue 1 (December 2015) - Maas, Marjo; van Dulmen, Simone; Sagasser, Margaretha; Heerkens, Yvonne; van der Vleuten, Cees; Nijhuis-van der Sanden, Maria; van der Wees, Philip
Abstract Background Clinical practice guidelines are intended to improve the process and outcomes of patient care. However, their implementation remains a challenge. We designed an implementation strategy, based on peer assessment (PA) focusing on barriers to change in physical therapy care. A previously published randomized controlled trial showed that PA was more effective than the usual strategy "case discussion" in improving adherence to a low back pain guideline. Peer assessment aims to enhance knowledge, communication, and hands-on clinical skills consistent with guideline recommendations. Participants observed and evaluated clinical performance on the spot in a role-play simulating clinical practice. Participants performed three roles: physical therapist, assessor, and patient. This study explored the critical features of the PA program that contributed to improved guideline adherence in the perception of participants. Methods Dutch physical therapists working in primary care (n  = 49) organized in communities of practice (n  = 6) participated in the PA program. By unpacking the program we identified three main tasks and eleven subtasks. After the program was finished, a questionnaire was administered in which participants were asked to rank the program tasks from high to low learning value and to describe their impact on performance improvement. Overall ranking results were calculated. Additional semi-structured interviews were conducted to elaborate on the questionnaires results and were transcribed verbatim. Questionnaires comments and interview transcripts were analyzed using template analysis. Results Program tasks related to performance in the therapist role were perceived to have the highest impact on learning, although task perceptions varied from challenging to threatening. Perceptions were affected by the role-play format and the time schedule. Learning outcomes were awareness of performance, improved attitudes towards the guideline, and increased self-efficacy beliefs in managing patients with low back pain. Learning was facilitated by psychological safety and the quality of feedback. Conclusion The effectiveness of PA can be attributed to the structured and performance-based design of the program. Participants showed a strong cognitive and emotional commitment to performing the physical therapist role. That might have contributed to an increased awareness of strength and weakness in clinical performance and a motivation to change routine practice.